Structural and Hemodynamic Analyses of Different Stent Structures in Curved and Stenotic Coronary Artery - Wei, Lingling; Leo, Hwa Liang; Chen, Qiang; Li, Zhiyong (Frontiers in Bioengineering and Biotechnology, 2019)
Coronary artery stenting is commonly used for the treatment of coronary stenosis, and different stent structures indeed have various impacts on the stress distribution within the plaque and artery as well as the local hemodynamic environment. This study aims to evaluate the performance of different stent structures by characterizing the mechanical parameters after coronary stenting. Six stent structures including three commercial stents (Palmaz-Schatz-shaped, Xience Prime-shaped, and Cypher-shaped) and three author-developed stents (C-Rlink, C-Rcrown, and C-Astrut) implanted into a curved stenotic coronary artery were investigated. Structural analyses of the balloon-stent-plaque-artery system were first performed, and then hemodynamic analyses were conducted within the deformed boundaries. The results show that among three commercial stents, the Palmaz-Schatz-shaped had the least stent dogboning and recoiling, corresponding to the greatest maximum plastic strain and the largest diameter change, nevertheless, it induced the highest maximum stress on plaque, intima, and media. From the viewpoint of hemodynamics, the Palmaz-Schatz-shaped displayed smaller areas of adverse low wall shear stress (< 0.5 Pa), low time-averaged wall shear stress (< 0.5 Pa), and high oscillating shear index (> 0.1). Compared to the Cypher-shaped, the C-Rcrown and C-Astrut had smaller recoiling, greater maximum plastic stain and larger diameter change, which indicated the improved mechanical performance of the Cypher-shaped stent. Moreover, both C-Rcrown and C-Astrut exhibited smaller areas of adverse low wall shear stress, and low time-averaged wall shear stress, but only C-Rcrown displayed a smaller area of adverse high oscillating shear index. The present study evaluated and compared the performance of six different stents deployed inside a curved artery, and has the potential to be utilized as a guide for the selection of suitable commercial stent for clinical application, and to provide an approach to improve the performance of the stents.